Management Of Bacterial Meningitis - Eka Gunadi (Jurnal Penelitian Perawat Profesional, 2020)
Bacterial meningitis is infection of meninges by bacteria which may spread to parenchym, ventricles, and along the spinal cord. The purpose of this literature review is to explain how to treat patients with meningitis bacterial. The references which are used in this review are 14 journal articles which were fetched from PubMed NCBI and Google Scholar by doing a literature searching , 4 books, and 1 thesis which all are published in range of 2009-2020. Keywords which were used in this literature searching were bacterial meningitis, epidemiology, and therapy. The references are further analzyed with systematic literature review which include activities such as collecting, evaluating, and the development of research with certain focus. The chosed articles shows that patient with meningitis bacterial should be treated carefully as he can spread pathogens via droplet and have his circulation and airway disrupted. Emphirical antibiotic must be administrated in 24 hours. Dexamethasone prescripton may be beneficial in some cases. In case of pneumococcal meningitis, management must include the seek for the source of infection and eradication of infection.